2004
DOI: 10.1111/j.1742-1241.2004.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote men with familial hypercholesterolaemia may have an abnormal triglyceride response post-prandially. Evidence for another predictor of vascular risk in familial hypercholesterolaemia

Abstract: Familial hypercholesterolaemia (FH) is associated with premature coronary heart disease (CHD). Post-prandial hypertriglyceridaemia has also been associated with cardiovascular disease. Thus, an abnormal post-prandial triglyceride (TG) clearance may contribute to the heterogeneity in the risk of CHD in heterozygous (h) FH. Therefore, we investigated the response of TG levels to a fatty meal in men with hFH. We studied 26 Greek men divided into two groups: the hFH group of 14 men, mean age 39 (SD = 11) years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
(53 reference statements)
3
20
1
1
Order By: Relevance
“…On the other hand, Watts et al [110] reported that the catabolism of CM remnants from plasma is not impaired in FH and that the hepatic uptake of these particles is not dependent on functional LDLR. If this is a case, the abnormal remnant accumulation should not have occurred in FH patients which is opposite to what was found by others [107,108] and our group [104].…”
Section: Fh and Postprandial Hypertriglyceridemiacontrasting
confidence: 76%
See 2 more Smart Citations
“…On the other hand, Watts et al [110] reported that the catabolism of CM remnants from plasma is not impaired in FH and that the hepatic uptake of these particles is not dependent on functional LDLR. If this is a case, the abnormal remnant accumulation should not have occurred in FH patients which is opposite to what was found by others [107,108] and our group [104].…”
Section: Fh and Postprandial Hypertriglyceridemiacontrasting
confidence: 76%
“…Moreover, in hFH subjects the production rate of the VLDL is increased and this is even more pronounced in FH homozygotes [104]. The VLDL production rate has been reported 50% higher in heterozygotes and 109% in homozygotes when compared with healthy controls [104].…”
Section: Fh and Postprandial Hypertriglyceridemiamentioning
confidence: 96%
See 1 more Smart Citation
“…The inclusion criteria for hFH women were clinical diagnosis of hFH [1], lack of CHD and the ability to walk on the treadmill at a moderate pace. They did not receive any medication, since they visited our Lipid Clinic for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute increase in TG seems similar between subjects with different levels of triglyceridemia and fasting TG are therefore the best predictor for non-fasting TG. It was also believed that TG variability increases in the non-fasting state, but the intraindividual variability of TG is not affected much throughout the day (22).…”
Section: Tgs: Daytime Rise and Fall And Its Effect On Ldl-cmentioning
confidence: 99%